Disaster Communication Based on Local Wisdom and Spirituality: A Case Study of The Eruption of Mount Agung, Bali - Amelita Lusia; Engkus Kuswarno; Johan Iskandar; Ninis Agustini Damayani (International Journal Labs, 2025)
Disaster communication strategies often overlook cultural and spiritual dimensions, leading to ineffective responses during crises. This study investigates the symbolic meaning of local wisdom and the role of spirituality in disaster communication and environmental conservation during the eruption of Mount Agung in Bali. The research analyzes how traditional symbols, local rituals, and informal communication channels enhance community preparedness and trust. Using a qualitative case study approach, data were collected through in-depth interviews with community members and local leaders and analyzed using the Miles and Huberman model. The findings reveal that traditional tools like kentongan (bamboo slit drums), animal behavior, and wooden house design serve as effective early warning systems rooted in community heritage. Local spirituality embodied by religious figures (Jero Mangku), collective rituals, the Tri Hita Karana philosophy, and customary law (Awig Gawi) fosters psychological resilience and communal trust. Furthermore, community radio and WhatsApp are proven to be effective communication tools, especially when coordinated by trusted local leaders. This research underscores the value of integrating spiritual and cultural components into disaster mitigation strategies. The findings offer valuable insights for developing community-centered, culturally grounded disaster communication frameworks in similar high-risk regions.